1977
DOI: 10.1111/j.1476-5381.1977.tb07543.x
|View full text |Cite
|
Sign up to set email alerts
|

The Β‐ADRENOCEPTOR STIMULANT PROPERTIES OF OPC‐2009 ON GUINEA‐PIG ISOLATED TRACHEAL, RIGHT ATRIAL AND LEFT ATRIAL PREPARATIONS

Abstract: I The f,-adrenoceptor stimulant properties of 5-(1-hydroxy-2-isopropylaminobutyl)-8-hydroxy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 20 publications
3
34
1
Order By: Relevance
“…It was less than those of procaterol and formoterol. Positive chronotropic effects and the selectivity ratio for isoproterenol and salbutamol in this study were practically com patible with those reported previously (6,16). The maximum positive chronotropic response to TA-2005 was about 80% of that of iso proterenol, and it was larger than those of procaterol and salbutamol.…”
Section: Selectivity For Tracheal Musclesupporting
confidence: 76%
See 2 more Smart Citations
“…It was less than those of procaterol and formoterol. Positive chronotropic effects and the selectivity ratio for isoproterenol and salbutamol in this study were practically com patible with those reported previously (6,16). The maximum positive chronotropic response to TA-2005 was about 80% of that of iso proterenol, and it was larger than those of procaterol and salbutamol.…”
Section: Selectivity For Tracheal Musclesupporting
confidence: 76%
“…Although the reason for this disagreement is not clear, possibilities are as follows: potent activity of TA-2005 on /Q2-adrenoceptor caused a positive chronotropic effect on the right atria which contains a significant popula tion (23%) of 82-adrenoceptors in contrast of the left ventricle (24). Secondly, antagonistic activities of salbutamol (17) and procaterol (6) …”
Section: Selectivity For Tracheal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several examples in the literature of agonists having selectivity for either the rate or force of cardiac contractions. Salbutamol and soterenol (Farmer, Kennedy, Levy & Marshall, 1970) and OPC-2009 (Yabuuchi, 1977) have been shown to exert preferential chronotropic activity in guinea-pig atria. In contrast, dopamine (Goldberg, 1972), dobutamine (Tuttle & Mills, 1975) and thyronamine (Boissier, Giudicelli, Larno & Advenier, 1973) have been found to exhibit inotropic selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, to explore the presence of f2-adrenoceptor subtypes in dog fat cells and to establish the validity of the model. Secondly, to compare in vivo the relative potencies of yohimbine, an O2-antagonist and procaterol, a highly selective f2-agonist (Yabuuchi, 1977;O'Donnell & Wanstall, 1985) with special attention being paid to their side-effects on the cardiovascular system and to various endocrinological and metabolic indices such as plasma glucose, insulin and catecholamines.…”
Section: Introductionmentioning
confidence: 99%